Major depressive disorder seven years after the conflict in northern Uganda: burden, risk factors and impact on outcomes (The Wayo-Nero Study) - Mugisha, James (BMC Psychiatry, 2015)
BACKGROUND: Major depressive disorder (MDD) is a major public health burden in conflict areas. However, it is not known for how long and by how much the observed high rates of MDD seen in conflict settings persist into the post-conflict period. METHODS: A cross sectional survey was employed seven years after the conflict in northern Uganda had ended in the three districts of Amuru, Gulu and Nwoya. RESULTS: The prevalence of major depressive disorder (MDD) was 24.7% (95% CI: 22.9%-26.4%). The distribution by gender was females 29.2% (95% CI: 14.6%-19.5%) and males 17.0% (95% CI: 26.9%-31.5%). The risk factors for MDD fell under the broad domains of socio-demographic factors (female gender, increasing age, being widowed and being separated/divorced); distal psychosocial vulnerability factors ( being HIV positive, low social support, increasing war trauma events previously experienced, war trauma stress scores previously experienced, past psychiatric history, family history of mental illness, negative coping style, increasing childhood trauma scores, life-time attempted suicide, PTSD, generalized anxiety disorder and alcohol dependency disorder) and the psychosocial stressors (food insufficiency, increasing negative life event scores, increasing stress scores). ‘Not receiving anti-retroviral therapy’ for those who were HIV positive was the only negative clinical and behavioral outcome associated with MDD. CONCLUSIONS: These findings indicate that post-conflict northern Uganda still has high rates for MDD. The risk factors are quite many (including psychiatric, psychological and social factors) hence the need for effective multi-sectoral programs to address the high rates of MDD in the region. These programs should be long term in order to address the long term effects of war. Longitudinal studies are recommended to continuously assess the trends of MDD in the region and remedial action taken.